Serious Journalism – The Value In The Media On The Polish Example - Hofman, Iwona (Communication Today, 2025)
The purpose of this article is to indicate signs of the dwarfism of journalism to the infotainment dimension and to determine the potential correlation between this problem and the specific treatment of professional integrity criteria forced by, among others, the pressure of free market, what can be an attempt to answer the question about the effects of replacing the traditional paradigm of journalism with the term “media product”. The main sources of the study are the statements of journalists publishing in Poland in the last decade. In theoretical grasp, it is a kind of informative and journalistic writing on topics relevant to the recipient in the global or local perspective, reliable with the force of the author’s authority. In the journalistic self-reflection, the most often provided equivalents of the serious journalism are the quality journalism, engaged, influential, neutral (especially in the political context), local and civil. However, the two last terms are used in relation to the new quality of media directed at the information from nearby and/or edited by people, groups trusting each other, which define themselves as ones which care for something (which do not want to continue being the passive consumers of the “media chaff”).